2018
DOI: 10.1002/2017ja024739
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Ionospheric Peak Electron Density During Sudden Stratospheric Warmings in the Arctic Region

Abstract: The focus of the paper is the ionospheric disturbances during sudden stratospheric warming (SSW) events in the Arctic region. This study examines the ionospheric behavior during 12 SSW events, which occurred in the Northern Hemisphere over 2006–2013, based on vertical sounding data from DPS‐4 ionosonde located in Norilsk (88.0°E, 69.2°N). Most of the addressed events show that despite generally quiet geomagnetic conditions, notable changes in the ionospheric behavior are observed during SSWs. During the SSW ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The variation in [O + /N2] ratio in the lower thermosphere changed the O + recombination rate, resulting in fluctuations in the ionospheric parameters. Yasyukevich (2018) showed an increase in the daytime GUVI [O/N2] along 88°E during the peak and decaying period of major warmings. Furthermore, Pedatella et al (2016), using numerical experiments and model simulations, revealed that enhancement in the migrating semidiurnal solar tide (SW2) during SSW modifies the lower thermosphere zonal mean circulation causing variations in [O/N2] ratio that induces a reduction in the Zonal and diurnal mean peak F layer electron density.…”
Section: Discussionmentioning
confidence: 99%
“…The variation in [O + /N2] ratio in the lower thermosphere changed the O + recombination rate, resulting in fluctuations in the ionospheric parameters. Yasyukevich (2018) showed an increase in the daytime GUVI [O/N2] along 88°E during the peak and decaying period of major warmings. Furthermore, Pedatella et al (2016), using numerical experiments and model simulations, revealed that enhancement in the migrating semidiurnal solar tide (SW2) during SSW modifies the lower thermosphere zonal mean circulation causing variations in [O/N2] ratio that induces a reduction in the Zonal and diurnal mean peak F layer electron density.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that the ionospheric variabilities during SSW period in the equatorial and low‐middle latitude regions are due to the modulation of vertical drift by PW and tide interactions as well as the direct impact of tidal waves (Goncharenko et al., 2010; Liu et al., 2011; Pedatella & Liu, 2013). As for the middle and high latitudinal regions, the neutral background wind changes, which are caused by the tides and SSW‐driven circulation, are significant sources for the ionospheric variations during SSW events (Pedatella et al., 2016; Yasyukevich, 2018; Yue et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The n(O)/n(N 2 ) ratio was calculated according to the results of calculations of the EAGLE model based on the calculation method used in the interpretation of the GUVI data [32]. The general properties n(O)/n(N 2 ) according to the results of the calculations and observation data are as follows: negative disturbances n(O)/n(N 2 ) during warming (21-25 January), which, according to [33], is the main cause of the observed negative disturbances foF2 at midlatitudes [34,35]; and positive disturbances n(O)/n(N 2 ) at midlatitudes after warming (27-31 January), which were noted earlier [36]. Thus, the EAGLE model successfully reproduces multiday trends (quasi-period ~20 days) of disturbances in the electron content and composition of the neutral atmosphere during and after the sudden stratospheric warming of 2009.…”
Section: Resultsmentioning
confidence: 76%